Pigouvian Concept Analysis Tax and Earmarking Tax in the Implementation of Motor Vehicle Tax - Tunisia, Farida; Inayati, Inayati (International Journal Labs, 2025)
The increasing ownership of motorized vehicles of the motorcycle type in DKI Jakarta, on the one hand, is a potential for vehicle tax revenue that contributes to regional taxes that can be used to improve road infrastructure, on the other hand, it causes problems of congestion and air pollution. The research method used is the literature study method to discuss about analysis concept the Pigouvian tax and earmarking tax in the implementation of motor vehicle tax policies. The results of the study indicate that the implementation of motor vehicle tax reviewed from the Pigouvian tax concept is in the application of progressive tax rates to control the negative external impacts caused by motor vehicles such as congestion, traffic accidents, air pollution, all of which cause social costs that tend to be greater in urban environments, one of which is in DKI Jakarta which has an impact on losses reaching IDR 100 trillion each year from the accumulation of excessive fuel consumption, corrected travel time losses due to congestion, the impact of air pollution caused by burning fuel oil and others. The implementation of motor vehicle tax reviewed from the earmarking tax concept, motor vehicle tax is included in the classification of fixed taxes with reference to a certain percentage of the minimum allocation of 10 percent intended for improving road infrastructure and transportation modes.